Anion Currents and Predicted Glutamate Flux through a Neuronal Glutamate Transporter - Otis, Thomas S. (J Neurosci, 1998)
Kinetic properties of a native, neuronal glutamate transporter were studied by using rapid applications of glutamate to outside-out patches excised from Purkinje neurons. Pulses of glutamate activated anion currents associated with the transporter that were weakly antagonized by the transporter antagonist kainate. In addition, kainate blocked a resting anion conductance observed in the absence of glutamate. Transporter currents in response to glutamate concentration jumps under a variety of conditions were used to construct a cyclic kinetic model of the transporter. The model simulates both the anion conductance and the glutamate flux through the transporter, thereby permitting several predictions regarding the dynamics of glutamate transport at the synapse. For example, the concentration-dependent binding rate of glutamate to the transporter is high, similar to binding rates suggested for ligand-gated glutamate receptors. At saturating glutamate concentrations, transporters cycle at a steady-state rate of 13/sec. Transporters are predicted to have a high efficiency; once bound, a glutamate molecule is more likely to be transported than to unbind. Physiological concentrations of internal sodium and glutamate significantly slow net transport. Finally, a fixed proportion of anion and glutamate flux is expected over a wide range of circumstances, providing theoretical support for using net charge flux to estimate the amount and time course of glutamate transport.